2016
DOI: 10.3945/ajcn.115.129650
|View full text |Cite
|
Sign up to set email alerts
|

No differential effect of beverages sweetened with fructose, high-fructose corn syrup, or glucose on systemic or adipose tissue inflammation in normal-weight to obese adults: a randomized controlled trial

Abstract: Excessive amounts of fructose, HFCS, and glucose from SSBs consumed over 8 d did not differentially affect low-grade chronic systemic inflammation in normal-weight to obese adults. This trial was registered at clinicaltrials.gov as NCT01424306.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 35 publications
2
36
0
4
Order By: Relevance
“…Feeding animals large amounts of fructose can rapidly produce multiple features of the metabolic syndrome, including obesity, dyslipidemia, fatty liver, hypertension, insulin resistance, and diabetes (18,19). Some, but not all, short-term dietary intervention studies in humans also demonstrate that overfeeding fructose, but not glucose, can increase visceral adiposity, postprandial hypertriglyceridemia, and insulin resistance, and effects on specific traits may be impacted by gender (20,21). One concern with such studies is that the amount Increased sugar consumption is increasingly considered to be a contributor to the worldwide epidemics of obesity and diabetes and their associated cardiometabolic risks.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding animals large amounts of fructose can rapidly produce multiple features of the metabolic syndrome, including obesity, dyslipidemia, fatty liver, hypertension, insulin resistance, and diabetes (18,19). Some, but not all, short-term dietary intervention studies in humans also demonstrate that overfeeding fructose, but not glucose, can increase visceral adiposity, postprandial hypertriglyceridemia, and insulin resistance, and effects on specific traits may be impacted by gender (20,21). One concern with such studies is that the amount Increased sugar consumption is increasingly considered to be a contributor to the worldwide epidemics of obesity and diabetes and their associated cardiometabolic risks.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the L/M ratio and lactulose recovery were "good" (ICC % 0.60). Of note, there was a significant difference in the mean L/M ratio by repeated measures ANOVA (13). Post hoc tests revealed that the L/M ratio obtained for HFCS was significantly different from both glucose and fructose, whereas glucose and fructose L/M ratios were not different from each other.…”
Section: Resultsmentioning
confidence: 77%
“…Although the intervention was not intended a priori for this purpose, the design provided repeated measures in up to 24 participants approximately 1 month apart, following an 8-day dietary period that was largely standardized. The one factor that differed between the three dietary periods (the type of sugar used to sweeten the SSBs) did not affect intestinal permeability or adipose tissue inflammation in a consistent manner, as discussed in the original publication (13). Therefore, this study provided an ideal opportunity to assess the reliability of repeated measures of these biomarkers.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations